Implementation of Blended Learning in Teaching English for Hospitality at Bali Crystal College - Danuarta Yoga*, I Gusti Ngurah Wahyu; Ratminingsih, Ni Made; Purnamika Utami, I Gusti Ayu Lokita (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to describe the results of implementing the Blended Learning model in teaching English for Hospitality course, and to determine students' perceptions of the implementation of the Blended Learning model. The subject of the research is the researcher himself. The data of this research are activities in the teaching and learning process using the Blended Learning in English model for friendliness and student perceptions of the learning process. The results of this study indicate that 1) Students and teachers are actively involved in the face-to-face learning process and online learning. 2) Students have a positive perception of blended learning model learning.